Fitting the facts of crime: an invitation to biopsychosocial criminology - Posick, Chad (Temple University Press, 2022)
Chapter 1. Introduction: the promise of biopsychosocial criminology for explaining the facts of crime -- Chapter 2. Sex differences in criminal behavior -- Chapter 3. Age differences in criminal behavior -- Chapter 4. Class differences in criminal behavior -- Chapter 5. Peer associations and social learning influences in criminal behavior -- Chapter 6. Social relationships, control, and criminal behavior -- Chapter 7. Stress and strain in criminal behavior -- Chapter 8. Criminal justice and law in criminal behavior and crime rates -- Chapter 9. Concluding remarks on the future of biosocial criminology.